Islam in Mahathir's Foreign Policy - Abdul Majid Hafiz, Mohamed; Abdullahi Ayoade, Ahmad (2017)
Malaysia during the tenure of Tun Mahathir Mohammed as the premier always has put Palestine and the Muslim states in the special place. It was during Mahathir’s era that sees the high commitment of the government towards the Palestine – Israel crisis as well as other issues in the Muslim states. This paper will attempt to analyze the influence of religion, Islam in this context, towards Malaysia’s involvement in these issues.